APPLICATION OF THE QUANTUM LEARNING MODEL WITH MIND MAPPING METHOD IN HIGH SCHOOL STUDENTS - Hasriyanti Hasriyanti; Wiwin Kobi (Universitas Negeri Gorontalo, 2022)
This study aims to determine 1) the application of the Quantum Learning learning model, 2) the differences in student interests and learning outcomes using the quantum learning model with the conventional model. This research is a quantitative descriptive type of research. The population of this study amounted to 240 students and a sample of 60 students. The experimental class has 30 students and the conventional class also has 30 students. The sampling technique is purposive sampling. Analysis of research data using descriptive statistical analysis, and infrensial analysis. The results showed that the experimental class students' interest in learning tended to be high with 82.97%. Meanwhile, the students' interest in learning in the control class tends to be low, with an average score of 54.85%. And the learning outcomes achieved by students on the subject matter of the atmosphere in the experimental class (taught using the quantum learning model) were in the good category, with an average of 76. The maximum value was 85 obtained and 65 the minimum value. Meanwhile for the control class ( taught by the teacher of the subject concerned using the lecture method) is in the sufficient category, with an average learning achievement of 62.8. The highest value achieved by students is 80 and the lowest value is 50